How does liquidity react to stress periods in a limit order market? - Helena Beltran; Alain Durré; Pierre Giot (National Bank of Belgium, 2004)
This paper looks at the interplay of volatility and liquidity on the Euronext trading platform during the December 2, 2002 to April 30, 2003 time period. Using transaction and order book data for some large- and mid-cap Brussels-traded stocks on Euronext, we study the ex-ante liquidity vs volatility and ex-post liquidity vs volatility relationships to ascertain if the high volatility led to decreases in liquidity and large trading costs. We show that the provision of liquidity remains adequate when volatility increases, although we do find that it is more costly to trade and that the market dynamics is somewhat affected when volatility is high.
Keywords: G10; C32; 330; order book; volatility; liquidity; Index-Futures; Aktienindex; Volatilität; Liquidität; Finanzsektor; Belgien